2014
DOI: 10.1007/s00709-014-0735-8
|View full text |Cite
|
Sign up to set email alerts
|

Rice terpene synthase 20 (OsTPS20) plays an important role in producing terpene volatiles in response to abiotic stresses

Abstract: This study examined the volatile terpenes produced by rice seedlings in response to oxidative stress induced by various abiotic factors. Solid-phase microextraction-gas chromatography-mass spectrometry (SPME-GC-MS) analyses revealed that when exposed to UV-B radiation, rice seedlings emitted a bouquet of monoterpene mixtures in a time-dependent manner. The mixtures comprised limonene, sabinene, myrcene, α-terpinene, β-ocimene, γ-terpinene, and α-terpinolene. Among them, (S)-limonene was the most abundant volat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 53 publications
2
31
0
Order By: Relevance
“…1A). These observations were consistent with previously reported RT-PCR results (Lee et al 2015). Moreover, the OsNAC10 expression was increased with increasing intensity of gamma-rays ( Fig.…”
Section: Ostps30 Expression Following Gamma Irradiationsupporting
confidence: 93%
See 4 more Smart Citations
“…1A). These observations were consistent with previously reported RT-PCR results (Lee et al 2015). Moreover, the OsNAC10 expression was increased with increasing intensity of gamma-rays ( Fig.…”
Section: Ostps30 Expression Following Gamma Irradiationsupporting
confidence: 93%
“…Several aspects regarding the genetic basis of plant-responses to ionizing radiation remain unknown. Lee et al (2015) reported that the expression levels of five OsTPS genes (i.e., OsTPS19, OsTPS20, OsTPS25, OsTPS26, and OsTPS30) are induced by gamma irradiation. However, OsTPS30 was not functionally characterized.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations